Pleiotropic and Potentially Beneficial Effects of Reactive Oxygen Species on the Intracellular Signaling Pathways in Endothelial Cells - Nadezhda Barvitenko; Elisaveta Skverchinskaya; Alfons Lawen; Elena Matteucci; Carlota Saldanha; Giuseppe Uras; Alessia Manca; Muhammad Aslam; Antonella Pantaleo (Antioxidants, 2021)
Endothelial cells (ECs) are exposed to molecular dioxygen and its derivative reactive oxygen species (ROS). ROS are now well established as important signaling messengers. Excessive production of ROS, however, results in oxidative stress, a significant contributor to the development of numerous diseases. Here, we analyze the experimental data and theoretical concepts concerning positive pro-survival effects of ROS on signaling pathways in endothelial cells (ECs). Our analysis of the available experimental data suggests possible positive roles of ROS in induction of pro-survival pathways, downstream of the Gi-protein-coupled receptors, which mimics insulin signaling and prevention or improvement of the endothelial dysfunction. It is, however, doubtful, whether ROS can contribute to the stabilization of the endothelial barrier.